1986
DOI: 10.1172/jci112578
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral glucose metabolism after portacaval shunting in the rat. Patterns of metabolism and implications for the pathogenesis of hepatic encephalopathy.

Abstract: The regional cerebral metabolic rate for glucose was measured in normal and portacaval shunted rats and the effects of unilateral carotid infusions of "threshold" amounts of ammonia were assessed. 8 wk after shunting the glucose metabolic rate was increased in all 20 brain regions sampled. Effects on subcortical and phylogenetically older regions of the brain were most pronounced with a 74% increase observed in the reticular formation at the collicular level. Increases in the cerebral cortex ranged from 12 to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

1989
1989
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(17 citation statements)
references
References 27 publications
1
16
0
Order By: Relevance
“…a References: (1) Cavanagh (1970), Cavanagh andKyu (1971), Williams et al (1972), Cremer et al (1975a, Sarna et al (1979); (2) Hindfelt et al (1977), Gjedde et al (1978), Ehrlich et al (1980), Duffy (1983), Cooper et al (1985), Cruz and Dienel (present study); (3) Lockwood et al (1986); (4) Hindfelt (1984); (5) Zanchin et al (1979Zanchin et al ( , 1981; Battistin and Zanchin (1980);Jeppsson et aI. (1983);Rigotti et al (1985); (6) Giguere and Butterworth (1984), Butterworth and Giguere (1986); Butterworth et al (1988);Girard and Butterworth (1992); (7) Holmin and Siesj6 (1974); (8) Mans et al (1982Mans et al ( , 1983aMans et al ( ,b, 1984aMans et al ( ,b, 1986aMans et al ( , 1990; White and Mans (1984).…”
Section: Lumped Constant In Shunted Ratsmentioning
confidence: 68%
See 1 more Smart Citation
“…a References: (1) Cavanagh (1970), Cavanagh andKyu (1971), Williams et al (1972), Cremer et al (1975a, Sarna et al (1979); (2) Hindfelt et al (1977), Gjedde et al (1978), Ehrlich et al (1980), Duffy (1983), Cooper et al (1985), Cruz and Dienel (present study); (3) Lockwood et al (1986); (4) Hindfelt (1984); (5) Zanchin et al (1979Zanchin et al ( , 1981; Battistin and Zanchin (1980);Jeppsson et aI. (1983);Rigotti et al (1985); (6) Giguere and Butterworth (1984), Butterworth and Giguere (1986); Butterworth et al (1988);Girard and Butterworth (1992); (7) Holmin and Siesj6 (1974); (8) Mans et al (1982Mans et al ( , 1983aMans et al ( ,b, 1984aMans et al ( ,b, 1986aMans et al ( , 1990; White and Mans (1984).…”
Section: Lumped Constant In Shunted Ratsmentioning
confidence: 68%
“…ICMRglc in many structures of fed, portacaval shunted rats assayed with the [14C]deoxygiucose (DG) method (Sokoloff et al, 1977) were previously reported to be depressed (6 of 36 structures) or un changed during the first few weeks after shunting, but to rise progressively to higher than normal val ues by 12 weeks in 25 of 36 structures (Cruz and Duffy, 1983). Lockwood et al (1986) also found in creases in ICMRglc assayed with the DG method in 8-week shunted rats, whereas ICMRglc when as sayed with [14C]glucose was reported to be reduced from 6 h to 8 weeks after shunting (Mans et aI., 1983b(Mans et aI., , 1986a(Mans et aI., , 1990Dejoseph and Hawkins, 199 1).…”
mentioning
confidence: 99%
“…Last, heterogeneous responses in different regions of CNS in PCS rats (Lockwood et al, 1986;Norenberg, 1987) and human with acquired HE (Kimura and Budka, 1986) have been described and it has been suggested that the capacity for ammonia removal by brain following PCS may be limited in certain brain regions (Butterworth et al, 1988). The explanation is unknown, but it must be remembered that CNS astrocytes are highly heterogenous (Miller, 1988;Wilkin et al, 1990) and the glutamine synthetase, enzyme responsible for ammonia detoxification, shows heterogeneity in their activity and distribution in different areas of the brain (Khelil et al, 1990).…”
Section: Discussionmentioning
confidence: 99%
“…Moderate hypoxia had no effect on glucose me tabolism or acid-base balance in the hemisphere with the intact carotid artery: LCMR g Ic and pH val ues were similar to normal values (Lockwood et al , 1986(Lockwood et al , , 1987aRoos and Boron, 1981). In the hemi sphere ipsilateral to the ligated carotid, there were marked abnormalities of both glucose metabolism and acid-base balance.…”
Section: Effects On Lcmrglc and Composite Tissue Phmentioning
confidence: 80%